AN ANALYSIS OF STUDENTS’ GRAMMATICAL ERRORS AND THE STRATEGIES TO COPE WITH THEIR ERRORS - Suci Ambarwati (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This article aims to describe the kinds of grammatical errors, to discover the sources of the errors, and to find out the strategies in grammatical errors. This study applied a descriptive qualitative research design. The subject was 28 students’ of the second-semester students of the English Department of Teacher Training and Education Faculty of the University of Islam Malang.  The instrumants of this study were students’ descriptive text and also use the questionnaires by Pawlak (2018). From the data, the total grammatical errors made by the students were 76 items, with 33 items or 43.4% omission errors, 21 items or 27.6% addition errors, 15 items or 19.7% misformation errors, and misordering 7 item or 9.2% misordering errors. Moreover, the grammatical errors  made by the students were caused by intralingual errors with 69 items, and interlingual with 7 items. It also could be seen that metacognitive and cognitive strategies are the most grammatical strategies that are used by the students, then followed by social strategies and affective strategies become the lowest strategies. To sum up, the student’s still lack of knowledge about grammar rules and mostly the errors are caused by intralingual factors. The suggestions from the researcher for the next researchers are to work more on the solutions of the sources of the errors made by the students and to find out the Grammar learning strategies that are appropriate for the students. Key Words : Error Analysis, Types of Grammatical Errors, Sources of Errors, Descriptive Text, and Grammar Learning Strategies